Rural Incarcerated Women: HIV/HCV Knowledge and Correlates of Risky Behavior. (December 2018) - Peteet, Bridgette; Staton, Michele; Miller-Roenigk, Brittany; Carle, Adam; Oser, Carrie
Rural incarcerated women have an increased risk of acquiring the human immunodeficiency virus (HIV) and the hepatitis C virus (HCV) due to prevalent engagement in drug use and sexual behaviors. Limited research has investigated HIV and HCV knowledge in this high-risk population. Furthermore, the interplay of sociodemographic factors (i.e., education, age, income, and sexual orientation) and risky behavior is understudied in this population. The present study evaluated a sample of adult, predominately White women from rural Kentucky ( n = 387) who were recruited from local jails. The sample had high HIV and HCV knowledge but also reported extensive risk behaviors including 44% engaging in sex work and 75.5% reporting a history of drug injection. The results of multiple regression analysis for risky sexual behavior indicated that sexual minority women and those with less HIV knowledge were more likely to engage in high-risk sexual behaviors. The regression model identifying the significant correlates of risky drug behavior indicated that HIV knowledge, age, and income were negative correlates and that sexual minority women were more likely to engage in high-risk drug use. When HCV knowledge was added to the regression models already including HIV knowledge, the interaction was significant for drug risk. Interventions for rural imprisoned women should consider the varied impact of sociodemographic background and prioritize HIV education to more effectively deter risky sexual and drug behaviors.